Accelerating Stunting Reduction by Empowering Posyandu Cadres and Village Officials in Monitoring Nutritional Status and Providing Additional Food to Pregnant Women - Aritonang, Evawany Y; Purba, Mauly; Panggabean, Sondang P; Manalu, Sarah Patumona; Manalu, Samuel MH (Talenta Publisher, 2024)
The low nutritional status of pregnant mother during pregnancy can result various adverse effects for mother and baby. Poor nutritional status in toddlers possible happen problems/delays development. In Dairi Regency has 189 toddlers (0.2 %) living in Bottom of the Line Red (BGM). Prevalence stunted toddlers in Dairi Regency in 2018 amounted to 23.3 %. That's why it's done empowerment cadres and village officials to monitor nutritional status and giving complementary food for pregnant mother and toddler to prevent stunting. Through increasing the knowledge and skills of cadres and village officials for achievement reducing the incidence of stunting in improving the nutritional status of pregnant women and toddlers can be done with nutritional surveillance by monitoring activities: recovery food complementary, administration of vitamin A, TTD, taburia, zinc, stimulation. This activity was attended by pregnant women, mothers of toddlers, cadres and village officials who were very enthusiastic about listening to the presentation by the service team about what is meant by stunting, its causes, treatment, and the role of cadres and village officials regarding the stunting problem. Discussions and questions and answers were also very interactive, showing the great attention paid to service activities. Apart from that, this service activity also provides complementary food to pregnant women and toddlers. Based on this, community service activities empowering the role of cadres and village officials to monitor nutritional status of pregnant mother and toddler for prevent stunting can increase knowledge and skills of partner in give knowledge and skills to pregnant and toddler for increase their nutritional status. It is hoped that this service activity can reduce the prevalence of stunting and other malnutrition problems.